Pembuatan Indeks Beranotasi Jurnal Subjek Ekonomi di Perpustakaan Fakultas Ekonomi Universitas Ekasakti Padang - Sri Novianti Putri; Elva Rahmah (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discuss about the process of making index with annotation the economic journal in the library of Fakultas Ekonomi, Universitas Ekasakti Padang. The aim of this study is to present or describe the process making index with annotation the economic journal in the library of Fakultas Ekonomi, Universitass Ekasakti Padang. The method used is the desscriptive method which is described what they are. The data has been collected through direct observation and asking some questions to the librarian in the library of Fakultas Ekonomi, Universitas Ekasakti Padang. Based on the the process of making index with annotation which are (a) the collection and selection of the journal in the library of Fakultas Ekonomi, Universitas Ekasakti Padang, after the collection and selection have been done, then the collection of the journal are 12 journals, 27 copies and 183 articles; (b) making description of the journal done by recording the data of index annotation. The informations that will be recording are the name of journal, volume, month, and years of published the journal, the title of articles, the authors, and page numbers of articles; (c) making annotation the articles, with the purpose to illustrate the content for the people. The process of making annotation done by reading all of the articles first, understanding the meaning of that articles, translates the abstract of articles journal into Indonesian language and concludes that; (d) established the keywords with the purpose to make easier in finding the informations. Keywords have been taken from the title of article, abstract, and the content of the article; (e) the construction of the index articles journal through some regulations of the author, the title of index, and the index keywords are arranged based on alphabetical order; (f) typing the index with annotation.Keyword: index with annotation, economic journal.